Convective Overstability in Radially Global Protoplanetary Disks. II. Impact on Planetesimal Formation - Marius Lehmann; Min-Kai Lin (The Astrophysical Journal)
The convective overstability (COS) is a hydrodynamic instability occurring in protoplanetary disk (PPD) regions with an adverse radial entropy gradient. It is a potential driver of turbulence and may influence planetesimal formation. In this second paper of our series, we study the effects of the COS on dust dynamics in radially global PPD simulations, focusing on the midplane region, where vertical gravity on the dust is included. Axisymmetric 2D simulations show susceptibility to both the COS and the vertically shearing streaming instability. For a Stokes number τ  = 0.1, strong dust clumping occurs only for highly supersolar initial metallicities Z  ≳ 0.05. In 3D nonaxisymmetric simulations, the COS generates large-scale, long-lived vortices that have the potential to efficiently concentrate dust, with dust accumulation strengthening as τ increases. For τ  = 0.01, no strong clumping occurs even at metallicities as high as Z = 0.1, and vortices remain robust and long-lived. At τ  ≈ 0.04, strong dust clumping is observed for solar metallicity ( Z = 0.01) and higher. For τ  = 0.1, clumping occurs even at strongly subsolar metallicities ( Z  ≳ 0.004), peaking at Z  ∼ 0.01–0.03, including solar values. Under these conditions, vortices weaken significantly. At higher metallicities ( Z  ≳ 0.04) with τ  = 0.1, large-scale vortex formation is suppressed, leading to nearly axisymmetric dust rings, which can still undergo clumping via the classical streaming instability.